Culturally Responsive Pedagogy: Connecting New Zealand Teachers of Science with their Māori Students. Issue 1 (22nd July 2010) - Glynn, Ted; Cowie, Bronwen; Otrel-Cass, Kathrin; Macfarlane, Angus
Abstract: This paper illustrates how important changes can occur in science learning and teaching if teachers take the trouble to understand and respect the cultural worlds of Indigenous students, and incorporate something of this understanding within their teaching practice. Ten teachers participated in a specially-designed one-year university postgraduate course, which encouraged them to incorporate into their classroom learning two Māori pedagogical principles, ako and whakawhanaungatanga. Ako is a responsive and reciprocal process, through which both teaching and learning roles are shared. Whakawhanaungatanga is the process of constructing relationships in the classroom between people, between students' cultural knowledge and domain knowledge. This paper draws on co-constructed narratives from four of the teachers, two Māori and two Pākehā (New Zealanders of European descent). The teachers built trusting and respectful relationships with their Māori students by facilitating connections between Western and Māori worldviews of science. They shared their teaching role with Māori elders ( kaumātua ) and members of the extended family of their students ( whānau ). The teachers learned a great deal from their Māori students who became highly engaged and agentic in their science learning. Students took collaborative responsibility for asking learning questions, and sought information on science topics from both Western and Māori worldviews.